Wrought iron grilles dating back to 1860 - Mumbai Archive Project Team (Jio Institute, 2024)
The wrought iron grilles on the boundary wall were installed in 1860 with the marking NRS, which stands for Nossa Senhora do Rosario, or “Our Lady of the Rosary”.